2002
DOI: 10.1007/bf03017920
|View full text |Cite
|
Sign up to set email alerts
|

La réponse de l’index bispectral à l’intubation endotrachéale est similaire chez les patients normotendus et hypertendus

Abstract: P Pu ur rp po os se e: : To compare the hemodynamic and bispectral index (BIS) responses to tracheal intubation in normotensive and hypertensive patients.M Me et th ho od d: : Three minutes after induction of anesthesia with thiamylal and fentanyl, tracheal intubation was performed in 24 normotensive and 22 hypertensive patients. Heart rate (HR), mean arterial pressure (MAP), and BIS were measured every minute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…(2001) studied fentanyl, alfentanil, remifentanil and sufentanil on the bispectral index during anesthesia with propofol in humans, and no significant difference was observed between the group that used fentanyl when compared to the placebo group. Similarly, Nakayama et al. (2002a,b) has reported that in human patients, the administration of fentanyl abolished the hyperdynamic effects of the surgical procedure during the administration of isoflurane without changing the values of BIS.…”
Section: Discussionmentioning
confidence: 88%
“…(2001) studied fentanyl, alfentanil, remifentanil and sufentanil on the bispectral index during anesthesia with propofol in humans, and no significant difference was observed between the group that used fentanyl when compared to the placebo group. Similarly, Nakayama et al. (2002a,b) has reported that in human patients, the administration of fentanyl abolished the hyperdynamic effects of the surgical procedure during the administration of isoflurane without changing the values of BIS.…”
Section: Discussionmentioning
confidence: 88%
“…The study design is not double-blinded; still the aim was to achieve equivalent depth of anaesthesia in both groups of patients by the use of the Cerebral State Index as an objective measure of anaesthetic depth. The cortical retrieved processed EEG index describes the balance between stimulation and anaesthetic depth [ 14 ] and also the interaction between analgesia and anaesthetics [ 7 ]. One may of course argue whether the groups were comparable with regard to depth of anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were pretreated with 1 mg/kg midazolam and 1 µg/kg fentanyl. Electrocardiography (EKG), pulse oximetry, body temperature, noninvasive Blood Pressure and Bispecteral Index (BIS) [6] were monitored (Bispectral index is one of several technologies which purport to monitor Depth of Anesthesia). The target RPP and Iso were set by entering the patients age and weight into the TCI unit.…”
Section: Subjectmentioning
confidence: 99%